DAMPAK DARI MUTASI, PROMOSI KARYAWAN DAN KOMPETENSI TERHADAP PENGEMBANGAN KARIR KARYAWAN - Yudi Eldovi Rakhman; Muhammad Alfani; Kurniaty Kurniaty (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The background of this study by the Employee Career Development ofNational Unity and the Politics of North Barito regency. This is affected bymutations employees, Promotion of Employment and competence of employees. Asfor the issue of this study is how much influence the mutation, Campaign Againstthe Occupation and Competence Career Development Officer at the National Unityand Politics of North Barito regency.The purpose of this study was to determine and analyze how muchinfluence the mutation, Job Promotion and competence either singly or jointly to theEmployee Career Development at the National Unity and Politics of North Baritoregency.The design of this study using quantitative methods. Data were collectedthrough questionnaires to 40 respondents in the apparatus of National Unity andthe Politics of North Barito regency by using sampling techniques proportionatestratified random sampling to determine the respondents to each variable.Results of the analysis found that the mutation variable (X1) of 40.2%,Promotions Position (X2) amounted to 63.8%, and Competence (X3) amounted to84.2% singly or together have a positive and significant impact on CareerDevelopment Employees (Y). Figures adjusted R-square of 0.892 indicates that89.2% Employee Career Development variables influenced by three independentvariables used in the regression equation. While the remaining 10.8% is explainedby other variables outside the three variables used in this study. And it is knownthat the dominant variable affecting Employee Career Development Competencyvariables are variables besides Mutations and Job Promotion.